Emergency department telemedicine consults decrease time to interpret computed tomography of the head in a multi-network cohort. (July 2021) - Swanson, Morgan B; Miller, Aspen C; Ward, Marcia M; Ullrich, Fred; Merchant, Kimberly AS; Mohr, Nicholas M
Introduction: Telemedicine can improve access to emergency stroke care in rural areas, but the benefit of telemedicine across different types and models of telemedicine networks is unknown. The objectives of this study were to (a) identify the impact of telemedicine on emergency department (ED) stroke care, (b) identify if telemedicine impact varied by network and (c) describe the variation in process outcomes by telemedicine across EDs. Methods: A prospective cohort study identified stroke patients in four telemedicine networks between November 2015 and December 2017. Primary exposure was telemedicine consultation during ED evaluation. Outcomes included: (a) interpretation of computed tomography (CT) of the head within 45 minutes and (b) time to administer tissue plasminogen activator (tPA). An interaction term tested for differences in telemedicine effect on stroke care by network and hospital. Results: Of the 932 stroke subjects, 36% received telemedicine consults. For subjects with a last known well time within two hours of ED arrival (27.9%), recommended CT interpretation within 45 minutes was met for 66.8%. Telemedicine was associated with higher odds of timely head CT interpretation (adjusted odds ratio = 3.03; 95% confidence interval (CI) 1.69–5.46). The magnitude of the association between telemedicine and time to interpret a CT of the head differed between telemedicine networks (interaction term p = 0.033). Among eligible patients, telemedicine was associated with faster time to administer tPA (adjusted hazard ratio = 1.81; 95% CI 1.31–2.50). Discussion: Telemedicine consultation during the ED encounter decreased the time to interpret at CT of the head among stroke patients, with differing magnitudes of benefit across telemedicine networks. The effect of heterogeneity of telestroke affects across different networks should be explored in future analyses.